2019
DOI: 10.1186/s12888-019-2065-z
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence is linked to post-traumatic growth after critical incidents in Austrian ambulance personnel

Abstract: BackgroundAmbulance personnel, as well as other emergency services like fire-fighters or the police force, are regularly confronted with experiences of extreme psychological distress and potentially traumatizing events in the line of their daily duties. As a consequence, this occupational group is exposed to an elevated risk of developing symptoms of Post-Traumatic Stress (PTSS). Subsequently, symptoms of Post-Traumatic Stress have been observed as potentially co-occurring with Post-Traumatic Growth (PTG) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 42 publications
(98 reference statements)
2
46
0
Order By: Relevance
“…Some authors suggest that SOC is a favoring factor for the mental health of care providers, as it relates to quality of life and protects against anxiety, depression, and subjective burden [46]. SOC has also been related with the prevention of post-traumatic stress experienced by healthcare professionals [47].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that SOC is a favoring factor for the mental health of care providers, as it relates to quality of life and protects against anxiety, depression, and subjective burden [46]. SOC has also been related with the prevention of post-traumatic stress experienced by healthcare professionals [47].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, some of the discussed factors may become subordinate as they might only explain minor proportions of redundant variance. Moreover, such studies should also include posttraumatic growth as an outcome measure since it is associated with both health-promoting factors [27] and psychopathological symptoms [102]. Furthermore, there is a strong need for longitudinal studies in representative samples addressing the predictive value of several health-promoting factors across a longer time.…”
Section: Future Researchmentioning
confidence: 99%
“…Moreover, recent meta-analyses underline SOC's role as a correlate of posttraumatic stress symptoms in various populations [25] and as a determinate of carer well-being in home care settings [26]. Consequently, higher levels of SOC are associated with lower levels of psychopathological symptoms [24] and enhanced posttraumatic growth [27] in medical staff. Similar associations of SOC and mental health problems have also been demonstrated for police officers [28] and firefighters [29].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, some of the discussed factors may become subordinate as they might only explain minor proportions of redundant variance. Furthermore, such studies should also include posttraumatic growth as an outcome measure as it has been shown to be associated with both health-benefitting factors [27] and psychopathological symptoms [96].…”
Section: Future Researchmentioning
confidence: 99%
“…Moreover, recent metaanalyses underline SOC's role as a correlate of posttraumatic stress symptoms in various populations [25] and as a determinate of carer well-being in informal care-giving [26]. Consequently, higher levels of SOC are associated with lower levels of psychopathological symptoms [24] and enhanced posttraumatic growth [27] in medical staff. Similar associations of SOC and mental health problems have also been demonstrated for police officers [28] and firefighters [29].…”
Section: Introductionmentioning
confidence: 99%